Becoming more transparent: Collecting and presenting data on biomedical Ph.D. alumni - Pickett,Christopher L; Tilghman,Shirley (PeerJ Preprints, 2018)
For more than 20 years, panels of experts have recommended that universities collect and publish data on the career outcomes of Ph.D. students. However, little progress has been made. Over the past few years, a handful of universities, including those in the National Institutes of Health’s Broadening Experiences in Scientific Training consortium, and organizations, including the Association of American Universities and the Association of American Medical Colleges, launched projects to collect and publish data on biomedical Ph.D. alumni. Here, we describe the outcome of a meeting, convened by Rescuing Biomedical Research, of universities and associations working to improve the transparency of career outcomes data. We were able to achieve consensus on a set of common methods for alumni data collection and a unified taxonomy to describe the career trajectories of biomedical Ph.D.s. These materials can be used by any institution, with little or no modification, to begin data collection efforts on their Ph.D. alumni. These efforts represent an important step forward in addressing a recommendation that has been made for decades that will improve the ability of trainees to better plan for their careers and for universities to better tailor their training programs.
Keywords: career outcomes transparency; PhD alumni; career taxonomy